(untitled) (Web of Teachers: Inderscience Research, 2024)
This article examines the general patterns of the path of historical development of human society on the basis of existing approaches in the philosophy of history and “Cyclism” on the basis of emergence, development, collapse and crisis. Timurid kingdoms. The shortcomings of Marx’s linear path of development, the cultural approach and the geographical approaches that explain the history of human society are also discussed, and a new author’s approach to explaining the history of human society and the causes of the crisis of the Timurid kingdom is described.